2005
DOI: 10.1080/00071660500098186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental vitamin E during the mature period on the reproduction performance of Taiwan Native Chicken cockerels

Abstract: One-day-old Taiwan native male chicks were fed with maize-soybean rearing diets without supplemental vitamin E to 23 weeks of age. From 23 to 52 weeks of age, the cockerels (n = 90) were assigned at random to 5 dietary treatments and fed with maize-soybean diets supplemented with 0, 20, 40, 80 and 160 mg/kg of vitamin E (dl-alpha-tocopherol acetate). Pullets (225) of the same age were fed with standard diets throughout. They were artificially inseminated with one dose of 0.04 ml/bird intact and 5-fold diluted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 30 publications
6
45
0
Order By: Relevance
“…The spermatogenic cell is the sum of spermatogenous cell, spermatocyte, spermatoblast and sperm male germ cells may be susceptible to oxidative stress because of high concentrations of PUFAs and low antioxidant capacity (Vernet et al, 2004). It is reported that dietary deficiencies of VE in growing males causes degenerative spermatogonium, resulting in a lower sperm concentration (Cooper et al, 1987;Lin et al, 2005). In this study, the density of spermatogenic cell in VE supplemented groups increased, that in Group 2 (200 IU sheep -1 d -1 ) was significantly higher than in Control (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The spermatogenic cell is the sum of spermatogenous cell, spermatocyte, spermatoblast and sperm male germ cells may be susceptible to oxidative stress because of high concentrations of PUFAs and low antioxidant capacity (Vernet et al, 2004). It is reported that dietary deficiencies of VE in growing males causes degenerative spermatogonium, resulting in a lower sperm concentration (Cooper et al, 1987;Lin et al, 2005). In this study, the density of spermatogenic cell in VE supplemented groups increased, that in Group 2 (200 IU sheep -1 d -1 ) was significantly higher than in Control (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Depending upon dietary supplementation the concentration of vitamin E in chicken semen varies from 0.46 μg/ml (no vitamin E supplementation) up to 1.04 μg/ml (vitamin E supplementation -200 mg/kg) as reported by Surai et al (1997).Vitamin E effectively scavenges free radicals producing stable ROOH groups. An increased level of vitamin E (160 mg/kg) in the chicken spermatozoa has been associated with a reduction in susceptibility to Fe +2 -induced lipid peroxidation (Lin et al, 2005).…”
Section: Vitamin E and Semen Qualitymentioning
confidence: 99%
“…Vitamin E is effectively transferred from the ration that is provided to breeders to the egg yolk (Lin et al, 2005;Vieira, 2007), indicating that supplementation in the rations of breeders increases the concentration of vitamin E in egg yolks and consequently in the tissues of chicks, which can reduce their susceptibility to lipid peroxidation. However, tissues could represent a limitation in the capacity of vitamin E storage, and the excess could be excreted (Kayden and Traber, 1993).…”
mentioning
confidence: 99%